2018
DOI: 10.1016/j.energy.2018.08.019
|View full text |Cite
|
Sign up to set email alerts
|

The direct interconnection of the UK and Nordic power market – Impact on social welfare and renewable energy integration

Abstract: United Kingdom and the Nordic power market have plans to interlink directly through a subsea power transmission line in The North Sea. Such power market couplings have complicated implications for the interconnected energy systems and for different agents in the common power market. We analyse this case by modelling the hourly operation of the Nordic-UK power market coupling, considering the local district heating (DH) system in each country as well. According to the results, after the operation of the new int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This includes interconnectedness of national energy systems, linkages with non-energy systems, and issues of emission responsibility. Stronger integration of national energy systems could reduce future costs of low carbon infrastructure, and increase system flexibility through grid interconnection (Zakeri et al, 2018). In most national contexts, the current and future impacts of climate change call for a deeper understanding of the importance of wider ecosystem services.…”
Section: Issue 2: Enhancing Model Functionalitymentioning
confidence: 99%
“…This includes interconnectedness of national energy systems, linkages with non-energy systems, and issues of emission responsibility. Stronger integration of national energy systems could reduce future costs of low carbon infrastructure, and increase system flexibility through grid interconnection (Zakeri et al, 2018). In most national contexts, the current and future impacts of climate change call for a deeper understanding of the importance of wider ecosystem services.…”
Section: Issue 2: Enhancing Model Functionalitymentioning
confidence: 99%
“…This study found that the average annual gas consumption per dwelling was considerably higher than the average electricity consumption. Although it is difficult to forecast future energy prices, it is anticipated that with future projected increase in renewable electricity generation and crossborder market integrations [65,66], the volatility in energy prices could be intensified and this might lead to variations in individuals' energy consumption patterns and their overall energy demand.…”
Section: Applications Of Empirical Load Profiles and Demand Diversity For Designing And Sizing Energy Infrastructuresmentioning
confidence: 99%
“…Equation (12) represents the conversion law and q jk,t is the heat demand in the DH network n in bidding area k. In order to formulate the problem in linear form, in (12), the heat supply of CHP technology i is coupled to the power supply of CHP technology p i,t by a heat-to-power ratio θ i,t . Equation (13) represents the constraints for the heat supply and H ikn,t is the available heat conversion capacity for the technology i in bidding area k in the DH network n. Finally, Equation 14represents the ramping constraints.…”
Section: Power and District Heating Sector Optimizationmentioning
confidence: 99%